DESIGN AND OPTIMIZATION OF PERMANENT MAGNET SYNCHRONOUS GENERATOR FOR USE IN HYDRODYNAMIC RENEWABLE ENERGY BY APPLYING ACO AND FEA - Nikbakhsh, Amir; Izadfar, Hamidreza; Alinejad Beromi, Yousef (IIUM Engineering Journal, 2017)
One of the most important ways to reduce fossil fuel consumption and consequently reduce greenhouse gases and environmental pollution is the use of renewable energies such as water, sun, wind, etc. One of the most efficient ways to take advantages of the shallow flowing waters such as rivers and fountains in electrical power generation is the use of hydrodynamic screw in the direction of water flow. The design of the generator for this application results in environmental dangers decrease. On the other hand, it provides some part of electrical energy required for human beings. Generators in hydrodynamic renewable energy system ought to have features such as high efficiency, power density and reliability as well as low volume. Among various generators, the permanent magnet synchronous generator (PMSG) meets these requirements very well. In this paper, first, analytical calculations and the design process of PMSG were explained. Then, the ant colony optimization (ACO) was used for the optimization of design quantities. PMSG design optimization increased in efficiency and decreased in volume. By improving these two parameters in the designed PMSG, it gets very suitable to be used in hydrodynamic renewable energy system. Finally, the results of the optimized design of PMSG were validated through simulation of it in Maxwell software and applying finite element analysis (FEA). Also the final results have been compared to similar experimental researches results.